Question:

If \( y = e^{-2x} \), then \( \frac{d^3y}{dx^3} \) is equal to:

Show Hint

When differentiating exponential functions of the form \( e^{ax} \), apply the chain rule repeatedly.
Updated On: Feb 11, 2025
  • \( 2e^{-2x} \)
  • \( e^{-4x} \)
  • \( 4e^{-4x} \)
  • \( -8e^{-2x} \)
Hide Solution
collegedunia
Verified By Collegedunia

The Correct Option is D

Solution and Explanation

Step 1: Differentiate \( y = e^{-2x} \): \[ \frac{dy}{dx} = -2e^{-2x}. \] Step 2: Differentiate again: \[ \frac{d^2y}{dx^2} = 4e^{-2x}. \] Step 3: Differentiate once more: \[ \frac{d^3y}{dx^3} = -8e^{-2x}. \]
Was this answer helpful?
0
0